ISTILAH-ISTILAH DALAM PERADILAN ISLAM - Putra, Eka (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2014)
Islamic Courts indeed have some sense of the terminology in the law. The terminology can be called by al-Qada al-adl / al-qist, al-hukm, al-iffa, and al-ijtihad. In this case, there are differences in the terms used in discussing and establishing a law. Because of differences all settings are based on existing ahwal and when it happens. The scope of the al-Qada is related to the implementation of syariah law in a particular case, which is intended for the realization of peace and well-being of the flesh. Formally, it was done by someone who is authorized to carry out these tasks in a particular area. The decision authorized person is obligated, with the meaning of words must be followed by those who stuck with what was decided that. The objective here is opposed to the wicked. People who transgress his testimony can not be accepted. Al-Hukm (plural al-Ahkam) is etymologically synonymous with al-Bukhari, al-fiqh, al-Qada bi al-adl. Al-Hukm also means arrested. Ijtihad is an ability to exert maximum effort to achieve something.Peradilan Islam sesungguhnya memiliki beberapa peristilahan dalam mengertikan hukum. Peristilahan itu bisa disebut dengan al-qada, al-adl/al-qist, al-hukm, al-iffa, dan al-ijtihad. Dalam hal ini ternyata terdapat perbedaan istilah yang dipakai dalam membahas dan menetapkan sesuatu hukum. Karena adanya perbedaan kasus-kasus itu. Semua penetapan itu didasarkan kepada ahwal yang ada dan terjadi ketika itu.Ruang lingkup al-qada adalah menyangkut pelaksanaan hukum syara dalam suatu kasus tertentu, yang bertujuan agar terwujudnya ketentraman dan kemaslahatan hidup duniawi. Secara formal hal itu dilakukan oleh seseorang yang diberi wewenang untuk melaksanakan tugas tersebut dalam wilayah tertentu. Keputusan orang yang berwenang tersebut sifatnya mengikat, dengan arti kata wajib dipatuhi oleh orang yang tersangkut dengan perkara yang diputuskan itu. Adil di sini merupakan lawan dari fasiq. Orang yang fasiq tidak dapat diterima kesaksiannya. Al-Hukm (jamaknya al-ahkam) secara etimologi sinonim dengan al-ilm, al-fiqh, al-qada bi al-adl. Al-Hukm juga bearti menahan. Ijtihad adalah mengerahkan suatu kemampuan secara maksimal untuk mencapai sesuatu.